Study on the Output Capacity of DISCO Variator - 崔正辉; 薛隆泉; 郗向儒 (Jixie chuandong)
The fundamental conception about output capacity of variator was expounded and variational tendency of the output capacity of DISCO variator was analysed in this paper. At the same time, we discussed the way of raising its load capacity, and finished its experimental research.